EVALUASI SISTEM PENDAFTARAN BERBASIS WEBSITE PADA PASIEN RAWAT JALAN DI RSUD DR. SOEROTO NGAWI DENGAN METODE TAM - Aprilia, Rizky; Dewiyani, A.A.I Citra; nurhadi, Nurhadi; Fadila, Rizki (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: In 2022, Dr. Soeroto Ngawi Regional General Hospital used website-based online outpatient registration. Since the implementation of the registration system, there has never been an official evaluation of this system, besides that observation by researchers there are still several problems that occur in the use of a website-based registration system. This study aims to evaluate its use by looking at perceptions of usefulness and ease of use using the TAM (Technology Acceptance Model) method. Subjects and Method: This type of research is quantitative analytic with a cross-sectional approach. Results: The results of data analysis on the perceived usefulness in the use of website-based registration at Dr. Soeroto Ngawi Regional General Hospital show that respondents agree that online registration at Dr. Soeroto Ngawi Regional General Hospital can be used effectively by outpatients. As for the perception of ease (Perceived Ease of use) of the 5 indicators, 2 of them disagree and 3 of them agree that online registration at the Dr. Soeoroto Ngawi Regional General Hospital can be used easily by outpatients. Conclusion: From the correlation test results, it can be concluded that perceived usefulness and ease of use affect user acceptance of the website-based outpatient registration system at Dr. Soeroto Ngawi Regional General Hospital.